Local Specialty Product Innovation of Tilapia Fish Nugget “Spirunila” through the Empowerment of Karangtaruna Pemuda Mudi Gabahan (PMG) and Persons with Disabilities in Mulur Village - Agung Setyarini; Sari Widati; Salsabila Amalia Putri Bumi; Fandi Galang Wicaksana; Sangga Rizki Ramadhan; Annisa Nur Safitri (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2025)
This community service program responds to the underutilization of tilapia production in Mulur Village, Sukoharjo, where limited product diversification constrains economic growth. The program introduced Spirunila, a fortified tilapia-based product, while empowering the PMG Youth Organization and persons with disabilities through an Inclusive Joint Business Group (KUBA). The Participatory Learning System (PALS) was implemented to deliver capacity-building activities in production technology, entrepreneurship, and digital marketing. Program effectiveness was evaluated using pre- and post-test questionnaires on seven indicators, which were analyzed using a Paired Sample t-Test, N-Gain Score, and Cohen’s d. The results showed statistically significant improvements (p < 0.001), high learning gains (N-Gain category: High), and substantial effect sizes (d > 1.97), demonstrating strong behavioral and capability transformation among partners. Institutional strengthening ensures sustainability through shared production governance and digital market expansion. The findings confirm that inclusive innovation in community-based fish processing can enhance rural economic diversification and reinforce village tourism competitiveness.